Assessment Of Heavy Metal Pollution Within Downstream Of Perak River Basin Using Gis Mapping - Zaki, Mahani Mohamad (Universiti Sains Malaysia, 2021)
The objectives of the study are to measure selected water quality parameters in the downstream section of the Perak River basin. Next, to calculate the Total Maximum Daily Load (TMDL) of the measured water quality parameters to estimate the mobility and dispersion of these pollutants. Lastly, to map the transport and dispersion of the pollutants using GIS Mapping. Four tests were conducted in the laboratory, which are turbidity, Total Suspended Solid (TSS), Total Kjeldahl Nitrogen (TKN), and heavy metal (ICP-OES). These tests involved 36 samples from the Downstream of Perak River Basin. The results showed that turbidity concentration ranges from 23.51 to 87 NTU, TSS concentration ranged from 30.67 to 742 mg/L, and TKN concentration ranged from 0.45 to 4.93 mg/L. 19 heavy metals were present when analyzed using Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES). The descending order of heavy metal was Ca > Mg > Cu > Fe > TI > Pb > Mn > Sr >V > Ti > Mo >Sb > Ni > Cr > As > Be > Co > Li > Cd. Heavy metal was chosen in the Total Maximum Daily Load (TMDL) technique to met the target water quality by doing pollution reduction analysis. The spatial distribution of all parameters was analyzed in ArcGIS 10.3.1 to get the geostatistical prediction map. Therefore, water quality testing is crucial in environmental monitoring, as it will significantly impact on ecosystems and aquatic life.